Leadership change design: a professional learning community (PLC) project in eastern Indonesia - Teddy Trilaksono; Ambara Purusottama; Ifa Hanifah Misbach; Irfan Hary Prasetya (Institute of Advanced Engineering and Science, 2019)
A professional learning community (PLC) is a long-term sustainable program that can replace professional development (PD) to enable teachers to become teacher leaders and school principals to become instructional leaders. Using a case study from the establishment of the PLC project in 10 schools of Eastern Indonesia (Saparua island, Maluku), this research develops a progressive leadership change model through an ADDIE instructional design that changes school leadership. The research aims to investigate how to identify the most effective leadership change model by exploring differrent forms of learning communities between school principals and teachers. Using an action research approach to solve the problem, the data were collected over a 10-month period when the PLC project activities took place and embedded them as empirical materials that complement each other. The findings show that the leadership change design through PLC runs effectively if value alignment occurs between school principals and teachers after the open environment is established. The data also highlight that aligned values must be embedded as school identities, whereas a school principal must act as a change leader in order to ensure that these changes are sustainable. This study concludes by proposing policy recommendations for policy makers and education stakeholders on how to develop PD and PLC in Indonesian schools.